1999
DOI: 10.1093/jnci/91.9.763
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated p53 Gene Transfer in Advanced Non-Small-Cell Lung Cancer

Abstract: Repeated intratumoral injections of Ad-p53 appear to be well tolerated, result in transgene expression of wild-type p53, and seem to mediate antitumor activity in a subset of patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
194
0
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(198 citation statements)
references
References 21 publications
1
194
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][32][33][34] Additionally, in clinical trials, the restoration of wild-type p53 gene does not always lead to tumor regression or tumor growth inhibition. [8][9][10] Hence, there exists a need for identification of alternative candidates for effective gene therapy, in particular under conditions where p53 is ineffective. When p73 was identified, it was reported that p73 is not induced by DNA damage, 11 but later on it was found that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][32][33][34] Additionally, in clinical trials, the restoration of wild-type p53 gene does not always lead to tumor regression or tumor growth inhibition. [8][9][10] Hence, there exists a need for identification of alternative candidates for effective gene therapy, in particular under conditions where p53 is ineffective. When p73 was identified, it was reported that p73 is not induced by DNA damage, 11 but later on it was found that p73 is indeed induced by a wide variety of DNA-damage-inducing drugs like adriamycin, etoposide, cisplatin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Moreover, in clinical trials the restoration of wild type p53 gene does not always lead to tumor regression or tumor growth inhibition suggesting resistance of some tumors to exogenous p53. [8][9][10] p73 is a member of p53 gene family and encodes proteins, which have significant homology with p53 both structurally and functionally. p73 can bind to p53 responsive elements and upregulate some of the p53 target genes suggesting that it has the potential for functional overlap with p53.…”
mentioning
confidence: 99%
“…71,72 Wtp53 -mediated tumor growth inhibition is a complex process. These findings have demonstrated that wtp53 -induced tumor regression may be due, at least in part, to antiangiogenesis mediated through the downmodulation of bFGF -BP.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In addition, several clinical trials with replication-deficient adenoviruses that express p53 have demonstrated an excellent safety profile. [10][11][12][13][14][15] Recently, such a vector has been approved for clinical application in China and several phase 3 trials are ongoing in the United States. However, overall, the efficacy of this approach has been relatively low.…”
Section: Introductionmentioning
confidence: 99%